Fiscal episodes in the economic and monetary union: Elasticities and non-Keynesian effects - Afonso, António (2022)
We estimate short- and long-run elasticities of private consumption for fiscal instruments, using a fixed-effects model for the 19 Euro area countries during the period of 1960–2017, to assess how fiscal elasticities vary during fiscal episodes. According to the results, positive ‘tax revenue’ elasticities indicate that consumers have Ricardian behaviour, whereby they perceive an increase in taxation to be a sign of future government spending. ‘social benefits’ appear to have a non-Keynesian effect on private consumption. In addition, using a narrative approach to identify fiscal consolidations, it is seen that private consumption continues to exhibit a non-Keynesian response to tax increases, both in the short and long-run, and ‘other expenditures’ have a recessive impact during ‘normal times’. Furthermore, ‘social benefits’ are more contractionary in consolidations than in both expansions and ‘normal times’. In addition, after the launch of the Economic and Monetary Union, expansionary fiscal consolidations became harder to observe, and ‘other expenditure’ and ‘investment’ lost their non-Keynesian role.